The Role of Social Media Influencers in China Beauty Industry: Consumers’ Perspective - CAO, XUEQIN (2019)
This study aims to explore the role of social media influencers in China beauty industry from the perspective of consumers. Existing literature on the topic mainly focus on the role of social media influencers in promoting products or building consumers customer relationships and brand awareness. The primary platforms being studied by scholars are also some social media platforms in the Western. Therefore, this study emphasizes on the beauty industry in the context of the Chinese market, including probing the social media platforms Chinese consumers use, consumers’ psychological mechanism in using beauty products, and the role social media influencers play in consumers selecting and purchasing beauty products. The study utilises in-depth interview technique of qualitative research method to seek consumers’ perceptions about the aspects mentioned above.